Are Clinical Outcomes of Microdissection Testicular Sperm Extraction in Non-Obstructive Azoospermic Men Affected by the Use of Fresh or Frozen Gametes? - Luk ROMBAUTS; Fabrizzio HORTA; Sandra HOLDEN; Darren KATZ; Mark GREEN; Deirdre ZANDER-FOX (Fertility & Reproduction, 2022)
Background: Non-obstructive azoospermia (NOA) is a severe form of male factor infertility, evident in approximately 5% of infertile couples seeking fertility treatment. The combination of microsurgical testicular sperm extraction (mTESE) and ICSI has become one of the treatment options, with sperm motility positively associated with outcome success rates. Few studies have investigated whether use of fresh or thawed gamete combinations affect clinical outcomes. Aim: To determine the clinical outcomes of ICSI cycles using mTESE recovered testicular sperm of NOA patients and whether these are affected by the use of fresh or thawed gametes. Method: A retrospective study of NOA patients who underwent mTESE between March 2017 and September 2020. Clinical outcomes investigated included successful surgical sperm retrieval (SSR), sperm motility, fertilisation, embryo utilisation and live-birth/ongoing pregnancy rates. Results: A total of 105 NOA patients underwent mTESE, with a 65.7% successful SSR. In total 58 patients contributed to 72 ICSI cycles, with a 37.5% 2PN fertilisation rate and 29.4% live-birth/ongoing pregnancy rate. Cycles using only motile sperm had a greater fertilisation rate than those using a motile/non-motile sperm combination (51.7% vs 31.1%, p[Formula: see text]0.05). Compared with fresh, thawed testicular spermatozoa didn’t affect clinical outcomes, including live-birth/ongoing pregnancy rates (Fresh 18.2%; Thawed 17.9%; Odds ratio (OR) 1.02 (0.34-2.86) p=0.98). In contrast, use of thawed oocytes decreased fertilisation rate [Fresh-oocytes: 45.0%; Vitrified-oocytes: 35.5%; OR 1.47(1.03-2.10), p=0.03] but had no differences for other clinical outcomes, including live-birth/ongoing pregnancy rate (p=0.74). Importantly, injection of exclusively non-motile-spermatozoa (n=26 cycles) resulted in a very low fertilisation rate (2.7%) and no live-birth/ongoing pregnancies were recorded. Conclusion: Microdissection TESE is an effective treatment for NOA patients, with no clear negative effects of using thawed spermatozoa, however, the use of vitrified oocytes requires further investigation. The use of non-motile spermatozoa in mTESE ICSI cycles is discouraged.